ANALYSIS OF CUSTOMER SATISFACTION SOPO GORGA CAFE AND RESTAURANT PEMATANGSIANTAR - Marisi Butarbutar; Efendi Efendi; Sudung Simatupang; Rosalinda Septiani Sitompul; Alex Lumbanraja (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
Abstract. This study aims to analyze customer satisfaction of Sopo Gorga Cafe and Resto Pematangsiantar. Research method with survey, data collection through interviews and questionnaires. The unit of analysis in this study was 42 customers as a sample. Data were analyzed with qualitative analysis. The results showed that customers were satisfied but not optimal, with the highest dimension on price, and the lowest dimension on product quality. To optimize customer satisfaction, it can be done by adding unique and interesting garnishes or toppings to the food or beverage products served. Keywords: analysis, satisfaction, and customers.Abstrak. Penelitian ini bertujuan menganalisis kepuasan pelanggan Sopo Gorga Cafe dan Resto Pematangsiantar. Metode penelitian dengan survei, pengumpulan data melalui wawancara dan kuesioner. Unit analisis pada penelitian ini adalah 42 orang pelanggan sebagai sampel. Data dianalisis dengan analisis kualitatif. Hasil penelitian menunjukkan bahwa pelanggan sudah puas namun belum optimal, dengan dimensi tertinggi pada harga, serta dimensi terendah pada kualitas produk. Untuk mengoptimalkan kepuasan pelanggan dapat dilakukan dengan menambah garnish atau topping yang unik dan menarik pada produk makanan atau minuman yang disajikan.Kata Kunci: analisis, kepuasan, dan pelanggan.